Phacoemulsification and Intraocular Lens Implantation Before, During, or After Canaloplasty in Eyes with Open-Angle Glaucoma: 3-Year Results. Issue 3 (March 2015) - Tetz, Manfred; Koerber, Norbert; Shingleton, Bradford J.; von Wolff, Kurt; Bull, Holger; Samuelson, Thomas W.; Lewis, Richard A.
Abstract : Purpose: To report 3-year results evaluating the effect on safety and efficacy of canaloplasty to treat open-angle glaucoma when combined with cataract surgery. Patients and Methods: This was a retrospective subset analysis of a prospective, international, multicenter study evaluating 133 eyes of 133 adult, open-angle glaucoma patients who underwent canaloplasty with tensioning suture placement. Eighty-two phakic eyes that received canaloplasty alone were compared with 51 eyes that underwent cataract surgery before or during canaloplasty. Results: Phakic eyes that received combined cataract-canaloplasty surgery (phacocanaloplasty) had a mean±SD baseline IOP of 23.5±5.2 mm Hg and mean glaucoma medication usage of 1.5±1.0 decreasing to a mean IOP of 13.6±3.6 mm Hg on 0.3±0.5 medications at 3 years postoperatively. Pseudophakic eyes undergoing canaloplasty had a mean baseline IOP of 23.9±5.2 mm Hg on a mean of 1.8±0.8 glaucoma medications decreasing to 15.6±3.5 mm Hg on 1.1±0.8 medications at 3 years. In phakic eyes, reductions in IOP were significantly greater and less postoperative IOP lowering medication was needed after undergoing phacocanaloplasty compared to eyes which had canaloplasty alone. Conclusions: Clear corneal phacoemulsification performed before or in combination with canaloplasty is a safe and effective surgical procedure to reduce IOP in adult patients with open-angle glaucoma.